SURVIVAL MECHANISM VICTIM HOUSHOLD OF LUMPUR LAPINDO IN SIDOARJO - JAWA TIMUR - Daulay, Pardamean (Jurnal Organisasi Dan Manajemen, 2010)
Emerged mud deposited by a heat in around the location of eksploration natural gas PT. Lapindo property in Kecamatan Porong Sidoarjo, it gave a extraordinary uncommon impact on the social environment and economics society on around. For sustain life its household, it conducted survival mechanism. This research purpose for describe of survival mechanism conducted by victim household of lumpur Lapindo. This research use qualitative approach with case studies strategy and data collecting conducted comprises deep interviewing on 10 victim household of lumpur Lapindo. The research result that survival mechanism conducted by victim of lumpur Lapindo, that (1) conducted economizing, (2) using manpower of family, include manpower of children, (3) using social network, (4) using outpouring of victim Lapindo location being promise a tour, (5) strategy the instigation of migration being last choised, and (6) public mobilitation of demontration and demonstrasi for fighting their land compensation. The research result to many influence choised survival mechanism factor that conducted, that (1) did not stabil household earnings, (2) a narrow opportunities for employment, (3) a damaged infrastructur and economic accses, (4) handling victim of lumpur walked slowly, and (5) cultural social of society condition who still haved family uinion society and strong social solidary. Many survival mechanism used that being their helped and gived life expectancy in the future.